Environmental impacts of bioenergy wood production from poplar short‐rotation coppice grown at a marginal agricultural site in Germany. Issue 7 (21st January 2017) - Schweier, Janine; Molina‐Herrera, Saúl; Ghirardo, Andrea; Grote, Rüdiger; Díaz‐Pinés, Eugenio; Kreuzwieser, Jürgen; Haas, Edwin; Butterbach‐Bahl, Klaus; Rennenberg, Heinz; Schnitzler, Jörg‐Peter; Becker, Gero
Abstract: For avoiding competition with food production, marginal land is economically and environmentally highly attractive for biomass production with short‐rotation coppices (SRCs) of fast‐growing tree species such as poplars. Herein, we evaluated the environmental impacts of technological, agronomic, and environmental aspects of bioenergy production from hybrid poplar SRC cultivation on marginal land in southern Germany. For this purpose, different management regimes were considered within a 21‐year lifetime (combining measurements and modeling approaches) by means of a holistic Life Cycle Assessment (LCA). We analyzed two coppicing rotation lengths (7 × 3 and 3 × 7 years) and seven nitrogen fertilization rates and included all processes starting from site preparation, planting and coppicing, wood chipping, and heat production up to final stump removal. The 7‐year rotation cycles clearly resulted in higher biomass yields and reduced environmental impacts such as nitrate (NO3 ) leaching and soil nitrous oxide (N2 O) emissions. Fertilization rates were positively related to enhanced biomass accumulation, but these benefits did not counterbalance the negative impacts on the environment due to increased nitrate leaching and N2 O emissions. Greenhouse gas (GHG) emissions associated with the heat production from poplar SRC on marginal land ranged between 8 and 46 kg CO2 ‐eq. GJ −1 (or 11–57 Mg CO2 ‐eq. ha −1 ). However, if the produced wood chips substitute oil heating, up to 123 Mg CO2 ‐eq. ha −1 can be saved, if produced in a 7‐year rotation without fertilization. Dissecting the entire bioenergy production chain, our study shows that environmental impacts occurred mainly during combustion and storage of wood chips, while technological aspects of establishment, harvesting, and transportation played a negligible role.